Qualitative Approach of the Scrutiny in Educational Psychology - Rodríguez Fuentes, Antonio (2019)
It was difficult for the interpretive opposing approach to fight the previous exclusive current with its ideographic approach to the study of a now subjective reality, which was consolidated and applied to practice with the transformative intention of the complementary socio-critical approach2, and through some of the qualitative methods: a) in the first approach, through the participant or non-participant ethnographic observation, instrumental, institutional, individual or collective study cases that provide understanding rather than previous description; b) in the second one, through the research-action or research based on the design that reverts the situation studied to free and improve it.